Effects of intravenous methylprednisolone therapy on leukocyte and soluble adhesion molecule expression in MS - Droogan, A G; Crockard, A D; McMillan, S A; Hawkins, S A (Neurology, 1998)
Intravenous methylprednisolone (IVMP) may inhibit inflammatory cell recruitment to active MS lesions by effects on leukocyte or endothelial cell adhesion molecule expression. We investigated 15 MS patients in relapse receiving a 5-day course of IVMP (500 mg/day) and 15 normal subjects. Patients' blood samples were obtained pretreatment, at 6 and 24 hours after the first dose, and 48 hours after completion of therapy. Levels of L-selectin, leukocyte functional antigen 1 (LFA-1), Mac-1, and very late activation antigen 4 (VLA-4) expression were determined on alphabeta and gammadelta T cells and monocytes by dual-color immunofluorescent flow cytometry. Serum levels of soluble (s) L-selectin, sE-selectin, soluble intercellular adhesion molecule 1 (sICAM-1) and soluble vascular cell adhesion molecule 1 (sVCAM-1) were measured by ELISA. There was a marked decrease in the T-cell and monocyte counts at 6 hours after therapy, with recovery to baseline at 24 to 48 hours. Adhesion molecule expression was normal on circulating T cells and monocytes in active MS. IVMP resulted in significant changes in the percent adhesion molecule expression on monocytes: increased L-selectin expression at 24 hours, decreased Mac-1 expression at 6 hours, and decreased VLA-4 expression at 6 hours and 24 hours following treatment. T-cell adhesion molecule expression was unaffected by the therapy. Serum sE-selectin was reduced at 6 hours and 24 hours following treatment. IVMP alters the distribution and kinetics of monocyte adhesion molecule expression and endothelial cell release of E-selectin, which may limit monocyte recruitment to areas of tissue destruction in MS.